The antitheatrical discourse in Ukrainian metadrama in the early twentieth century - Kocherga, Svitlana; Visych, Oleksandra (Przegląd Wschodnioeuropejski, 2020)
The article analyzes methods of implementing antitheatrical discourse in Ukrainian dramaturgy. Different types of antitheatricality in literary texts are distinguished on the basis of plays by M. Starytskyi, I. Karpenko-Karyi, A. Krushelnytskyi, V. Vynnychenko, Ya. Mamontiv, V. Cherednychenko, and M. Kulish. The authors define key vectors that the antitheatrical discourse follows: criticism of theater as an institution, criticism of the drama school / method, criticism of theatricality and acting, including in offstage situations. It is arguably reasonable to examine the phenomenon of antitheatrical prejudice in the context of the theory of metadrama as one of its factors. Artistic interpretation of the theater in an ironic or farcical vein, discussions over the repertoire that is no longer relevant, the aesthetic nature of stage technique, and discredit of acting as an occupation all generally encourage dramatic conventionality to double. Most common metadramatic devices used to implement antitheatricality in Ukrainian drama are believed to include a play within a play, adaptation of spectator’s reception for stage, and intertextual references.